NONFIGURATIVE APPROACH: SUSTAINABLE ADAPTIVE REUSE TO RESPOND TO CITY’S EVOLUTION - Baskoro Laksitoadi; E C Cattaneo (TATALOKA, 2019)
This paper describes an approach of adaptive reuse on an abandoned buildings due to the rapid changes of economy and policy in the city. The keyword ‘nonfigurative’ is used because this approach is focused on creating connections and relationship rather than a physical building. Two other keywords are also used to support it. ‘Contextual’ means that history, spirit of place (genius loci), and existing set of rules given by the existing building are the key starting point while ‘flexible’ means that the product of this approach must have the ability to respond to the ever-changing needs of a city. Nowadays, buildings are left obsolete far earlier that its life span initially assumed. This situation often leaves us with ruins in the landscape or even in the middle of our city. In the era of uncertainty where city evolves swiftly due to the rapid changes of economy, policy, and technology, we believe that a nonfigurative approach is a sustainable way to respond to this problem. It will be able to maximize the unexplored potential of an obsolete or even an abandoned building, and equip them with the ability to evolve along with the city.